Symptoms of overexploitation in the stock of the Norway lobster (Nephrops norvegicus) on the "Serola Bank" (western Mediterranean Sea off Barcelona) - Sardá, Francisco (Scientia Marina, 1998)
A comparison of the mean sizes for the Norway lobster population on the Serola Bank indicated a decrease of 4 mm CL in males and 3.6 mm CL in females over the past 20 years. This means a reduction between 1 and 2 years in the age of the catches. Discussion considers this aspect as symptomatic of overexploitation of this resource in the general context of the area, where CPUE for this species has suffered a significant decrease in recent years.